Effects of Seawater Corrosion and Freeze-Thaw Cycles on Mechanical Properties of Fatigue Damaged Reinforced Concrete Beams - Zijian Liu; Bo Diao; Xiaoning Zheng (Advances in Materials Science and Engineering)
The effects of seawater corrosion and freeze-thaw cycles on the structural behavior of fatigue damaged reinforced concrete (FDRC) beams were experimentally studied. Results show that the residual strength of FDRC beams reduces as the fatigue load level (the ratio of maximum fatigue load to the ultimate static load) increases. The reduction in the loading capacity of FDRC beams in atmosphere environment was about 6.5% and 17.8% for given fatigue load levels of 0.2 and 0.3, respectively. However, if FDRC beams are exposed to the environment of seawater wet-dry cycles or to the environment of alternating actions of freeze-thaw and seawater immersion, as expected during the service life of RC bridge structures in coastal regions or in cold coastal regions, a more rapid reduction in the strength and stiffness of the beams is observed. The significance of an accurate simulation of working load and service condition RC bridge structures in coastal regions and cold coastal regions is highlighted.